Mixed epithelial and stromal tumor of the middle ear: The first case report - Michal, Michael; Skálová, Alena; Kazakov, Dmitry V; Pecková, Květoslava; Heidenreich, Filip; Grossmann, Petr; Michal, Michal (Human pathology, 2017)
We report a tumor arising in the middle ear of a 65-year-old female patient that was composed of an ovarian-type stroma (OS) and an epithelial component. The tumor consisted of irregular, polypoid masses containing multiple variably sized cystic spaces, which were invariably surrounded by the OS. The cystic spaces were lined by flat, cuboidal, or columnar epithelial cells, in most parts showing mucinous differentiation. The epithelial lining of the cysts strongly expressed cytokeratins AE1-3, CK7, CK8, CK18, CK19, EMA, and S100 protein. The stroma expressed CD34 and smooth muscle actin. No cytological atypia or mitoses were present, and the proliferative activity was less than 1% in both components. The clonality analysis proved the clonal nature of the neoplasm. We believe that this tumor is a new member in the family of neoplasms containing the OS, and therefore we propose the term mixed epithelial and stromal tumor of the middle ear.
Keywords: terminologie jako téma; Terminology as Topic; proliferace buněk; Female; buňky stromatu; střední ucho; výsledek terapie; ženské pohlaví; Tomography, X-Ray Computed; biopsie; Immunohistochemistry; lidé; Molecular Diagnostic Techniques; Epithelial Cells; Ear Neoplasms; Treatment Outcome; Ear, Middle; imunohistochemie; Humans; Neoplasms, Complex and Mixed; nádory ucha; diagnostické techniky molekulární; nádorové biomarkery; Aged; Biopsy; Stromal Cells; Cell Proliferation; Biomarkers, Tumor; nádory komplexní a smíšené; senioři; epitelové buňky; počítačová rentgenová tomografie